Evaluation of Familiarity with Financial Investigation Approaches and Emerging Audit Innovations Among Practitioners: An Exploratory Inquiry - Dr. Andika Pratama (International Interdisciplinary Business Economics Advancement Journal, 2026)
The increasing complexity of financial systems, coupled with the proliferation of corporate fraud and technological disruption, has significantly elevated the importance of forensic accounting and advanced auditing technologies. This study investigates the level of familiarity among accounting practitioners with financial investigation techniques and emerging audit innovations. Grounded in an exploratory research framework, the study synthesizes theoretical perspectives and empirical findings from existing literature to assess awareness, adoption, and practical challenges associated with modern auditing tools and forensic methodologies.The research integrates insights from forensic accounting theory, technological auditing frameworks, and corporate governance mechanisms to construct a multidimensional understanding of practitioner competency. It critically evaluates the role of artificial intelligence, data analytics, and automated auditing systems in enhancing fraud detection efficiency and audit quality. Drawing upon prior studies, including those examining forensic accounting effectiveness (Alshurafat et al., 2021; Nursansiwi, 2023), technological audit transformation (Eulerich et al., 2023; Fedykl et al., 2022), and financial irregularities in emerging economies (Roy, 2016; Pandey & Vinjamuri, 2022), the study identifies key determinants influencing practitioner awareness and capability.The findings indicate a moderate level of conceptual awareness but a significant gap in practical implementation and technical proficiency. While practitioners acknowledge the importance of forensic accounting techniques, their adoption remains constrained by limited training, technological barriers, and organizational resistance. Additionally, the integration of emerging technologies such as AI-driven audit tools is uneven, reflecting disparities in institutional readiness and regulatory support.The study contributes to academic discourse by bridging the gap between theoretical advancements and practical application in forensic accounting and auditing. It also provides actionable insights for policymakers, educational institutions, and professional bodies to enhance training frameworks and promote technology-driven audit practices. Ultimately, the research underscores the necessity of continuous professional development and institutional transformation to align practitioner competencies with evolving financial investigation and auditing paradigms.